Growth cycles with or without price flexibility - Peter Skott (University of Massachusetts, Department of Economics, 2015)
This note - written in response to von Arnim and Barrales (2015) - shows that (i) the Kaldor-Goodwin models in Skott (1989a, 1989b) and Skott and Zipperer (2012) provide good approximations to models with fast but finite adjustment of prices, (ii) the models can generate cyclical patterns that match the stylized facts, and (iii) an alternative model with instantaneous output adjustment and fixed prices produces a dynamic system that is virtually identical to the Kaldor-Goodwin; this model may describe parts of the service sector
Keywords: E12; E32; 330; Endogenous cycles; Harrodian instability; price flexibility; rationing; labor hoarding; behavioral foundations